국가교육과정 종교 교과의 신종교 서술 고찰 -대순진리회 관련 사례를 중심으로 - 김은영; Kim Eun-young (大巡思想論叢, 2024)
This study investigates the depiction of new religions in the public sphere, with a specific focus on their representation within the national curriculum in Korea. To pinpoint particular phenomena, an analysis of the national curriculum revisions and textbooks related to religions centered around Daesoon Jinrihoe (大巡眞理會) was conducted. Through this examination, this study introduces Korean new religions as a novel topic for religious education research in secondary schools. Simultaneously, it assesses whether the educational objectives align with the intended goal of providing an objective liberal arts education. The recent direction in revising religious education and related curriculum aims to avoid promoting adherence to a specific religion, emphasizing instead the enhancement of objective knowledge about diverse religions and civic literacy. However, this shift has not substantially influenced the portrayal of Korean new religions. The earliest descriptions of Daesoon Jinrihoe found in textbooks published during the sixth national curriculum merely mention it as a sect of Jeungsan-religions (甑山敎), with variations in content and table across publishers. Additionally, in textbooks such as Religious Studies published by municipal ministries of education, Daesoon Jinrihoe is only described as a contemporary new religion involved in social activities. These instances highlight the inconsistency in the changing narratives regarding new religions in the educational sector. Improvements in representing new religions are necessary to enhance the religious literacy of Korean society beyond a narrow focus on Daesoon Jinrihoe's propagation. Lastly, this research suggests an integrated analysis of the description of Daesoon Jinrihoe in the national curriculum, including adjacent subjects and public communication, such as research and the dissemination of reference materials for the publication of future textbooks. 본 연구에서는 우리나라 중등 종교교육의 신종교에 대한 서술의 구체적 현상을 파악하기 위해 종교 교과 개정의 변천과 교과서들을 대순진리회 사례를 중심으로 탐색했다. 이러한 시도를 통해 중등학교에서의 종교교육 연구의 새로운 주제로서 신종교를 제시하고, 동시에 객관적 교양교육을 지향하는 교과교육으로서 그 목표의 구현 여부를 분석한 것이다. 그동안 종교 교과의 개정 방향은 특정 종교의 신도 양성을 지양하고, 종교에 대한 객관적 지식과 시민적 소양을 함양시키는 것에 중점을 두어왔다. 그러나 이러한 변천은 신종교 서술에는 큰 영향을 미치지 못 하였다. 대순진리회를 실례로 본다면, 제6차 교육과정에서 발행된 교과서들에서부터 최초로 증산교의 분파 정도로 간략하게 소개되었으며 발행처별로도 그 분량과 체계에 차이가 있었다. 또한, 시도교육청 주도로 발행된 가장 최근의 『종교학』 교과서에서의 대순진리회는 활발한 사회활동을 하는 현대 종교의 모습을 중심으로 기술된다. 이를 통하여 학교교육 현장의 신종교 서술에는 특정할 만한 기준이 없으며, 국가교육과정 개정에 따른 변화에도 일관성이 없었음을 확인할 수 있었다. 지금까지의 단절되고 파편화된 신종교 교육 경향은 우리 사회의 종교문해력 증진을 위해서도 개선이 요구된다. 이를 위한 향후 과제로서 인접 교과를 포함한 국가교육과정 개정 참여, 향후 교과서 발행을 위한 참고자료 연구와 확산과 방안을 제시하였다.